Camp Pocono Trails 2011: counseling at a weight loss camp - Strathe, Gretchen (My University, 2015)
Summer 2011 was a life changing experience, not only for the four hundred adolescents struggling with their weight, but also for me, a camp counselor and nutritionist at Camp Pocono Trails. During my stay at camp, I witnessed a population-wide cry for help. The campers not only needed physical help to keep their weight in check, but many were also dealing with psychological issues, such as eating disorders, anxiety and depression. Over two month course at camp, I became part of a support system for an entire division of teenage girls, ages sixteen to nineteen, as they developed both physically and mentally. An absolutely incredible and humbling experience.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Strathe, G. (2011). Camp Pocono Trails 2011: counseling at a weight loss camp. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Camps for overweight children--Pennsylvania--Reeders; Nutrition counseling; Obesity in adolescence; Camp Pocono Trails (Reeders, Pa.); Reports; Reports